Preface to Geriatric Oral Research Group Conference Papers - H. Asuman Kiyak, MA, PhD; Michael 1. MacEntee, DDS, PhD (Blackwell Synergy, 2000)
On March 14-16,1999, the Geriatric Oral Research Group of the International Association of Dental Research held a satellite symposium entitled ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œSuccessful Aging Through Oral Health.ÃƒÂ¢Ã¢â€šÂ¬Ã‚Â The rustic and quiet setting of the conference on Vancouver Island created an ideal venue for focusing on oral health issues that will affect future cohorts of older adults, not just in North America, but throughout the world.